Implementasi Metode Material Requirment Planning (MRP) Dalam Melakukan Perencanaan Persediaan Bahan Baku Kursi Susun Pada CV XYZ - Arifa Yuriyadi; Siti Muhimatul Khoiroh (International Forum of Researchers and Lecturers, 2023)
CV XYZ is a company engaged in manufacturing with production in the form of stacking chairs. This company has a production capacity of 200 units of stacking chairs every day. The company has 3 types of bunk chairs, namely CH-100 KR, CH-200 KR, and CH-200 PC. Customer demand at this company tends to be fluctuating (up and down) which results in the company experiencing difficulties in determining the optimal raw material inventory to meet customer needs. The Material Requirement Planning (MRP) method is an appropriate method for scheduling inventory. The result of this scheduling model is in the form of a master production schedule (JIP) which is used to determine the demand for chair products for the next 6 months. The results of data processing obtained requests for stacking chairs in the next 6 months for the type CH-100 KR 10.724 unit, CH-200 KR of 10.998 unit, and CH-200 PC of 9.687 unit. The demand is then calculated using the MRP approach with LFL and EOQ. An effective material requirements planning method with the lowest cost is to use the Lot For Lot (LFL) method which gives the lowest cost results IDR 7,475,617,611.